Multiculturalism in the Quran (Tafsir Siyasy Analysis Q.S Al-Hujarat Verse 13) - AMIN, Moh; KAUNAIN, Muflih Fahmi (Integration: Journal Of Social Sciences And Culture, 2023)
Purpose: This article discusses multiculturalism by analyzing the contemporary interpretation of Q.S Al-Hujarat verse 13, which is the rationale for the diversity of human backgrounds in Islam.Methodology: The methodology used is descriptive analysis with the type of qualitative research- literature study, which uses references related to contemporary interpretation and multiculturalism thoughts Q.S Al-Hujarat verse 13. The theory used in this article is the Contemporary Method of Interpreting the Quran from Abdullah Saeed, a contemporary interpretation method to analyze verses related to the latest social, political, and other societal problems.Findings: Abdullah Saeed's tafsir theory was chosen because this tafsir is a tafsir that has a contextual and renewable interpretation method in looking at current social problems in particular and universally.Implication: The result of this article is that two values reflect multiculturalism in the Quran. First is the value of Inclusiveness and Plurality, which is the fundamental value of diversity that humanity must own. Second, Justice and Equality must be applied in life indiscriminately.